Potential Resistance to Oxaliplatin-Based Regimens in Gastric Cancer Patients with ERBB2 R678Q Mutation: Evidence from a National Genomic Database - Shuhei Suzuki; Manabu Seino; Hidenori Sato; Yosuke Saito; Koki Saito; Yuta Yamada; Koshi Takahashi; Ryosuke Kumanishi; Tadahisa Fukui (Current Issues in Molecular Biology, 2025)
Epidermal growth factor receptor 2 (ERBB2/HER2) is a critical biomarker in gastric cancer management, but the clinical implications of specific ERBB2 mutations remain poorly characterized. Methods/Results: We investigated the ERBB2 R678Q mutation, utilizing the Center for Cancer Genomics and Advanced Therapeutics (C-CAT) database, which involved the analysis of 3116 gastric/gastroesophageal junction adenocarcinomas. ERBB2 mutations were identified in 130 cases, with R678Q present in 40 patients. These patients exhibited significantly lower response rates to oxaliplatin-based regimens compared to ERBB2 wild-type cases (19.0% vs. 38.0%, p = 0.03), while other ERBB2 mutations demonstrated no such resistance. No significant differences in the response were observed to the ramucirumab or nivolumab regimens. Conclusions: Our findings suggest that the ERBB2 R678Q mutation may predict a poor response to oxaliplatin-based therapy. This study provides real-world evidence supporting the potential clinical relevance of this specific ERBB2 mutation in treatment decision making for gastric cancer.